2020
DOI: 10.23939/jtbp2020.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Integral Regulating Parameters of a Bladder-Type Hydraulic Accumulator

Abstract: Main factors influencing the regulating parameters of gas-charged hydraulic accumulators are thermodynamic processes occurring during the gas compression and expansion. Method of experimental determination of the polytropic index of gas processes in the hydraulic accumulator is improved. An experimental setup was installed for the investigation of integral regulating parameters of the bladder-type hydraulic accumulator. The parameters of non-stationary expansion of the air in the accumulator's shell during its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Using hydraulic accumulators is useful due to the shortage of the number of pump switches, thus providing the increasing of its service life. Hydraulic accumulators are widely used in engineering: in water supply and other fluid pressure systems (Shi et al [1]; Zhuk et al [2]), in the power engineering (Morozov et al [3]), in hydro-drives (Bravo et al [4]; Kumar et al [5]; Puddu and Paderi, [6]; Wu et al [7]), etc. Parameters of transitional gas processes have a significant impact on the efficiency of the relevant engineering systems (Juhala et al [8]; Mamčic and Bogdevičius, [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using hydraulic accumulators is useful due to the shortage of the number of pump switches, thus providing the increasing of its service life. Hydraulic accumulators are widely used in engineering: in water supply and other fluid pressure systems (Shi et al [1]; Zhuk et al [2]), in the power engineering (Morozov et al [3]), in hydro-drives (Bravo et al [4]; Kumar et al [5]; Puddu and Paderi, [6]; Wu et al [7]), etc. Parameters of transitional gas processes have a significant impact on the efficiency of the relevant engineering systems (Juhala et al [8]; Mamčic and Bogdevičius, [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [15] demonstrated the applicability of the Soave-Redlich-Kwong adiabatic equation for gas-charged hydraulic accumulators. Zhuk et al [2], performed a theoretical analysis of gas processes inside the bladder-type water supply hydraulic accumulators widely used in automated pumping stations. A comparison of dimensionless storage volumes of the hydraulic accumulator, obtained for isothermal and adiabatic conditions, as well as for polytropic process with index .…”
Section: Introductionmentioning
confidence: 99%